Inter‐Ethnic Differences in the Efficacy and Safety of Tyrosine Kinase Inhibitors Used in Oncology: Insights From Phase 3 Clinical Trials - Nicki M. Kyriacou; Annette S. Gross; Andrew J. McLachlan (Clinical and Translational Science)
ABSTRACT Differences in the efficacy and safety of tyrosine kinase inhibitors (TKIs) have been observed across ethnic/ancestry subpopulations (previously reviewed to 2017). With an expanding number of TKIs approved since that time, an updated review of TKI response across ethnic/ancestry subpopulations in Phase 3 TKI clinical trials was conducted. A total of 73 population subgroup analyses (defined by participant race, ethnicity, ancestry or geographic region) of progression‐free survival (PFS) and/or overall survival (OS) were identified by a literature search. Twelve (16%) of the analyses investigating the efficacy of afatinib, brigatinib, dacomitinib, gilteritinib, lorlatinib, neratinib, osimertinib, or pazopanib were assessed to report population differences in PFS and/or OS. For 28 (38%) of the analyses that showed suggestions of a potential efficacy difference across subpopulations, limitations in the data available precluded further assessment. There were 17 (23%) analyses assessed to report comparable efficacy outcomes across diverse subpopulations. The majority of clinical trials noted no clinically remarkable differences in safety between subpopulations; however, for brigatinib, crizotinib, pazopanib, and sunitinib, distinct patterns of adverse events were reported in the Asian and non‐Asian subgroups. The underrepresentation of specific subpopulations, the grouping together of results of diverse subpopulations, as well as inconsistencies in the definition and reporting of participant ethnicity/ancestry are barriers to the meaningful exploration of inter‐ethnic differences in TKI response. Therefore, further insight into the associations between ethnicity/ancestry and TKI response will require an increase in the diversity of clinical trial participants and appropriate analysis and reporting of subpopulation results.